Beginning Hibernate - Ottinger, Joseph B.; Minter, Dave; Linwood, Jeff (Expert's voice in Java., 2014)
Beginning Hibernate, Third Edition is ideal if you're experienced in Java with databases (the traditional, or 'connected, approach), but new to open-source, lightweight Hibernate, a leading object-relational mapping and database-oriented application development framework. This book packs in information about the release of the Hibernate 4.x persistence layer and provides a clear introduction to the current standard for object-relational persistence in Java. And since the book keeps its focus on Hibernate without wasting time on nonessential third-party tools, you'll be able to immediately start building transaction-based engines and applications. Experienced authors Joseph Ottinger with Dave Minter and Jeff Linwood provide more in-depth examples than any other book for Hibernate beginners. The authors also present material in a lively, example-based manner not a dry, theoretical, hard-to-read fashion.